2021
DOI: 10.1007/s12063-021-00206-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of project’s initiatives focused on the reduction of environmental footprints during COVID-19: evidence from the United States firms

Abstract: In this paper, we examine whether the projects of the United States (U.S.) corporations have implemented initiatives to reduce the environmental footprint of their supply chains during coronavirus (COVID-19). Environmental footprint reductions could be achieved by reducing waste, reducing resource use, and reducing ecological emissions by introducing environmental management systems in the supply chains. For this aim, the project’s initiatives play a crucial role. This study has the primary purpose of examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Such innovations are significant in limiting the natural constraints and creating a sustainable competitive advantage for the firm. In addition, this result supports the finding of Dhiaf et al ( 2021 ) that initiatives to reduce harmful effects of business operations on the environment have a positive effect on business performance, especially in the context of Covid-19. At the same time, it enables the firm to achieve “premium price” by customers (Kim 2017 ) and “increased efficiency” (Melo and Garrido-Morgado 2012 ), minimizes potential financial risk, and enhances competitive advantage in a sustainable direction.…”
Section: Discussionsupporting
confidence: 88%
“…Such innovations are significant in limiting the natural constraints and creating a sustainable competitive advantage for the firm. In addition, this result supports the finding of Dhiaf et al ( 2021 ) that initiatives to reduce harmful effects of business operations on the environment have a positive effect on business performance, especially in the context of Covid-19. At the same time, it enables the firm to achieve “premium price” by customers (Kim 2017 ) and “increased efficiency” (Melo and Garrido-Morgado 2012 ), minimizes potential financial risk, and enhances competitive advantage in a sustainable direction.…”
Section: Discussionsupporting
confidence: 88%
“…Following prior literature, we use Tobin’s Q as the dependent variable to measure market performance (Atayah et al. , 2021a, b; Dhiaf et al. , 2021; Najaf et al.…”
Section: Method Sample and Datamentioning
confidence: 99%
“…Following prior literature, we use Tobin's Q as the dependent variable to measure market performance (Atayah et al, 2021a, b;Dhiaf et al, 2021;Najaf et al, 2021a;Najaf and Atayah, 2021;Najaf et al, 2021b). Tobin's Q is widely used in several studies as a proxy for market performance, and it does reflect not only the current company's profitability but also its future potential growth.…”
Section: Dependent Variablementioning
confidence: 99%
“…Fahimnia et al (2018) investigated the relationship and the trade-offs between a green supply chain with a degree of robustness and a robust supply chain with a degree of greening. Dhiaf et al (2021) indicate that firms that followed the environmental regulations showed better financial performance during COVID-19.…”
Section: Sustainability Issues In Supply Chainmentioning
confidence: 97%